2006
DOI: 10.1001/archpsyc.63.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Risk for New Onset of Depression During the Menopausal Transition

Abstract: The current study suggests that within a similarly aged population of women with no lifetime history of depression, those who enter the menopausal transition earlier have a significant risk for first onset of depression. Further studies are needed to determine more definitively whether other factors, such as the presence of vasomotor symptoms, use of hormone therapy, and the occurrence of adverse life events, independently modify this risk. Physical symptoms associated with the menopausal transition and mood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
484
3
19

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 734 publications
(521 citation statements)
references
References 60 publications
15
484
3
19
Order By: Relevance
“…The results that women with low CES-D at baseline may be particularly affected by the change in status are consistent with findings from two recent studies of women with low depressive symptoms at baseline (Freeman et al, 2006;Cohen et al, 2006). The current study has extended their findings by including five different ethnic groups and adjusting for the multiple relevant risk factors for depression, such as stressful events and inadequate social support, and examining the influence of the postmenopause on risk for high depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…The results that women with low CES-D at baseline may be particularly affected by the change in status are consistent with findings from two recent studies of women with low depressive symptoms at baseline (Freeman et al, 2006;Cohen et al, 2006). The current study has extended their findings by including five different ethnic groups and adjusting for the multiple relevant risk factors for depression, such as stressful events and inadequate social support, and examining the influence of the postmenopause on risk for high depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…9,10 Studies of women in the MT have shown that sleep disruption is a major contributor to decreased quality of life 6 and are an important reason women seek care for menopausal symptoms. 11,12 Large cohort studies, including SWAN, The Penn Ovarian Aging Study, and the Harvard Study of Moods and Cycles, have reported an increased risk for depressed mood in women going through the MT, [13][14][15] although the mechanism underlying this association is unclear. For both women and men, sexual activity decreases as a function of age.…”
Section: Introductionmentioning
confidence: 99%
“…Increased vulnerability for depression in women appears to begin with puberty and declines after the menopause (Soares et al, 2003a;Steiner et al, 2003). While there has been controversy as to whether the risk of depression increases during the perimenopause, recent carefully controlled studies have suggested that the perimenopause is associated with increased vulnerability for both depressive symptoms and a diagnosis of new onset depression (Cohen et al, 2006;Freeman et al, 2006) even among women with no prior history of affective disorders. While the reasons for the increased female vulnerability to mood disorders remain to be fully understood, the strongest candidate remains the influence of cycling levels of gonadal steroids on neurotransmitter systems and mood regulatory systems (Steiner et al, 2003), perhaps interacting with genetic vulnerability and life stress (Caspi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%